Camel research papers from Sudan - Musa, B.E.; Melaku, A.; Wilson, R.T. (International Livestock Centre for Africa, 1986)
Compilation of research papers dealing with the camels traditional husbandry methods, reproduction aspects, nutrition, pathology & use of camel meat as human food product in the Sudan.